2005
DOI: 10.1117/12.639223
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy on the ultrastructure of glioma cell

Abstract: OBJECTIVE :the main purpose of this experiment was to study the change of C6 glioma cells' ultrastructure treated by photodynamic therapy(PDT), observe the change of morphology METHOD :Make the model of rat glioma by transplanted C6 glioma cells into caudate nucleus,treated the glioma rat by PDT after two weeks. Observed the difference of subcellular structure before and after PDT by electron microscope. RESULT : Apoptosis and necrosis can be seen after treated by PDT in the C6 glioma, basal membrance damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The most significant damage was found in mitochondria, as reported before [19,22] . Swelling occurred in the cellular organs such as mitochondria and endoplasmic reticula in most cells treated with ALA alone or ALA plus iron chelators.…”
Section: Morphological Changesmentioning
confidence: 56%
See 1 more Smart Citation
“…The most significant damage was found in mitochondria, as reported before [19,22] . Swelling occurred in the cellular organs such as mitochondria and endoplasmic reticula in most cells treated with ALA alone or ALA plus iron chelators.…”
Section: Morphological Changesmentioning
confidence: 56%
“…The sections were post-stained with uranyl acetate and lead hydroxide. The sub-cellular structure was observed under transmission electron microscope (Hitachi H600, Japan) [19] . Ultrathin sections were obtained by using ultramicrotome PowerTome-XL (RMC, USA).…”
Section: Morphological Observationmentioning
confidence: 99%
“…Thus, glioma cells have the ability to take up photosensitizers. In an in vitro study, Hu et al (18) showed that HMME-mediated PDT could induce the apoptosis of C6 glioma cells and that calcium overload played an important role in extensive ultrastructural damage.…”
Section: Discussionmentioning
confidence: 99%
“…PDT's effect on the cultured glioma cells has been reported (Chopp et al, 1996;Hu et al, 2007;Karmakar et al, 2007;Sailer et al, 2007). However, not only malignant but also normal glial cells and neurons are damaged during PDT of brain tumors.…”
mentioning
confidence: 98%